Perancangan Sistem Informasi Penggajian Karyawan (Studi Kasus: PT. Sumber Mas Autorindo) Menggunakan Delphi XE4 - Sufajar Butsianto (Jurnal SIGMA, 2021)
The purpose of this study was to develop a model employee payroll system PT Sumber Mas Autorindo, as well as simplify the process data and salaries of precise, fast, and accurate. The method used is the method of literature and field. Library method is collecting data that support theoretical writing by searching for references related to employee payroll information system design. While the method comprising the field of observation and interview techniques. Mechanical observation of direct observation to the financial part of how the process of employee payroll today. Interview technique is to directly face to face with the parties concerned in dealing with employee payroll. The results that have been achieved is a system of employee payroll information to facilitate the processing of employee data and salary and speed in making statements salaries. Conclusion of research is the design by using Delphi programming language XE4 and Microsoft SQL Server 2008 R2 as its database can be designed a system of data processing employee payroll information on PT Sumber Mas Autorindo. In order for the application program that has been produced can be used as well as possible to assist employees in providing data information regarding payroll, expected to be developed further for use as needed. Keywords: Payroll Information System, Design Delphi, Payrol System, Delphi XE, Salary